Comparative effectiveness of combined antihypertensive and psychocorrective therapy in hypertensive men with anxiety and depressive disorders in the andropause period - O. V. Timofeeva; V. V. Skibitsky; A. V. Fendrikova (Российский кардиологический журнал, 2025)
Aim. To evaluate the effectiveness of two variants of combined antihypertensive therapy in combination with psychopharmacotherapy in hypertensive (HTN) men with anxiety and depressive disorders (ADD) in the andropause period.Material and methods. The study involved 67 men with uncontrolled HTN and ADD in the andropause period, of whom 35 with a median age of 57 [56; 63] years took a combination of "angiotensin-converting enzyme (ACE) inhibitor perindopril + calcium channel blocker (CCB) amlodipine + antidepressant (selective serotonin reuptake inhibitor) trazodone", and 32 patients with a median age of 58,5 [57; 61] years received "angiotensin II receptor blocker (ARB) candesartan + amlodipine + trazodone". All subjects underwent 24-hour ambulatory blood pressure monitoring (ABPM) at inclusion and after 6 months of therapy, and the most significant prognostic parameters of vascular stiffness and central aortic pressure (CAP) were assessed using the BPLabVasotens hardware complex (OOO Petr Telegin, Russia).Results. High antihypertensive and vasoprotective efficacy of both variants of combined pharmacotherapy in men with HTN and ADD in andropause was established. However, with the use of the combination of ACE inhibitor + CCB + antidepressant, more pronounced improvement of 24-hour BP profile, arterial stiffness and CAP were observed compared to patients receiving ARBs + CCB + antidepressant.Conclusion. When comparing the antihypertensive and vasoprotective efficacy of two variants of combined pharmacotherapy in men with HTN and ADD in the andropause period, certain advantages of the combination of ACE inhibitors + CCB + antidepressant were revealed. This was manifested in a more pronounced improvement in ABPM parameters, a decrease in arterial stiffness and CAP, than in patients receiving ARB + CCB + antidepressant.